Evaluating Children with Otitis Media for Bacteremia or Urinary Tract Infection - Daniel Yawman; Patrick Mahar; Aaron Blumkin; Gregory Conners (International Journal of Pediatrics)
Background. It is unclear if clinicians evaluate for concurrent bacteremia or UTI in young patients diagnosed with acute otitis media (AOM). Objectives. To describe how often, and under which circumstances, emergency providers investigate for bacteremia or UTI in 2–36 month olds with AOM. Methods. Cases of AOM were analyzed from the 2001–2004 National Hospital Ambulatory Medical Care Survey (NHAMCS)-Emergency Department dataset. Results. AOM was diagnosed in 17% of the 10,847 recorded visits of 2–36 month olds. Of these visits, laboratory testing included: CBC: 7%, Blood culture: 4%, urinalysis or urine culture: 5%, and any of these tests: 9%. Rates of testing for 2–6 month olds with temperature ≥ 38.0 (CBC: 13%, blood culture: 9%, urinalysis or urine culture: 7%, any of the tests: 14%) were not significantly different from testing of patients aged 6–12 months, or 12–36 months (all P>.1). Patients with temperature of ≥39.0 were more likely to have all tests, with the exception of urine investigation, than patients with temperature between 38.0 and 38.9. Conclusions. 17% of 2–36 month old patients seen in the emergency department are diagnosed with AOM. Investigating for bacteremia or UTI in these patients is not routine, even in febrile infants.